ANALISIS KESEDIAAN MEMBAYAR WILLINGNESS TO PAY (WTP) KONSUMEN TERHADAP PRODUK BATIK TULIS KHAS JOMBANG - Hidayah, Listiani; Ayu Nuning Farida Afiatna, Fatma (INVANTRI (Inovasi Dan Pengelolaan Industri), 2021)
In determining the selling price, it is important to know how much consumers' willingness to pay (WTP) to get Jombang Typical Batik Tulis products with better quality. In this regard, this study aims to determine the maximum average value of WTP that consumers are willing to pay in buying Batik Tulis Jombang Typical and to find out the significant factors that affect the WTP of Batik Tulis Jombang typical consumers. This study took a sample of 40 respondents who were consumers of Jombang's typical written batik products, and were selected using the purposive sampling method. The data were analyzed using the contingent valuation method (CVM) analysis and using multiple linear regression analysis. The results showed that the maximum average value of WTP for consumers of Batik Tulis Jombang typical was Rp 555,250.00 per piece. Among them, the factors that significantly influence consumers' willingness to pay are gender, income and price.